Yes or no, or How to answer a negative question - Gruet-Skrabalova, Hana (Linguistica (Ljubljana), 2016)
This paper deals with answers to negative yes-no questions, focusing on data from Czech. It is shown that answering particles can express both positive and negative answers to negative questions, but that their choice is not free. Several pieces of evidence are discussed in order to show that the use of the particles depends on the interpretation of negation in the question: expletive negation or true negation. This semantic distinction is furthermore tightly linked to the syntactic position of the negation, according to which we distinguish between negative interrogative clauses and negative declarative clauses used as questions. An analysis in terms of absolute and relative polarity is proposed to account for the mixed behaviour of answering particles: particles express absolute polarity in answers to interrogative questions, whose polarity is open, and relative polarity in answers to declarative questions, whose polarity has been already specified.
Keywords: češčina; členek; denial; négation; particule; semantics; semantika; sémantique; skladnja; syntax; syntaxe; zanikanje